Opportunities and constraints of the partner market and educational assortative mating - Stauder, Johannes; Kossow, Tom (Journal of family issues, 2021)
This study aims to determine to what extent the opportunities and restrictions of the partner market influence educational assortative mating. It also analyzes the interplay between the opportunity structure and preferences. Matching district-based partner market indicators to heterosexual couples when they move in together based on the German Socio-Economic Panel, we find strong effects of the opportunity structure on educational homogamy. The results further imply that the density of the supply of potential partners is more important for educational assortative mating than imbalanced supply and competition. While the impact of partner market imbalances on assortative mating is a mere effect of the opportunity structure, the effects of the partner market density of relevant and available partners in space weakly imply that homophile and maximization preferences are simultaneously at work.
Gesehen am 20.01.2022